NEW CANCER DIAGNOSES AMONG OLDER MEDICARE BENEFICIARIES. (11th November 2018) - Ornstein, K; Liu, B; Alpert, N; Taioli, E; Schwartz, R
Abstract: While cancer diagnoses are considered very stressful, little is known about the health status, functional limitations, caregiving needs, and quality of life (QoL) for older cancer patients. We used a prospective study design to (1) examine the health characteristics and QoL for older adults before a cancer diagnosis and (2) determine how these factors may change after diagnosis. Using the National Health and Aging Trends Study (NHATS), a national survey of older Medicare beneficiaries, linked to Medicare claims data, we identified 242 community-dwelling older adults with first cancer diagnosis identified in Medicare claims: lung(32%), breast(20%), prostate(30%), and colorectal(18%). Before diagnosis (mean=10 months), patients reported receiving an average of 25 hours of help/ week and 29% reported poor/fair health. Almost one-third were living alone, 17% received help with at least one activity of daily living (ADL), 9% had probable dementia; and they had 3 comorbidities, on average. Among the 138 individuals with post-cancer diagnosis interviews (mean=6 months), the percentage of those who experienced depression symptoms increased from 11% to 23% (p<0.0001), those who experienced anxiety symptoms increased from 8% to 16% (p<0.0001), those who experienced pain increased from 48% to 55% (p<0.0001), and amount help received changed from 29 hours per week to 36 hours per week (p=0.21). Older adults receiving their first cancer diagnoses may already have significant functional and clinical impairment and reduced QoL. Health-related QoL factors such as depression, anxiety and pain should be addressed at the time of diagnosis as these difficulties may increase over time.